Pendekatan Analitik terhadap Filsafat Pendidikan Orang Dewasa - Fattah Hanurawan (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1998)
Analytic Approach to the Philosophy of Adult Education. In their philosophical activities, analytic philosophers emphasize the analysis of concepts, arguments, slogans, statements and normative philosophy in order to make normative or descriptive statements about the world, human beings, and human behaviors and actions. Analytic philosophy of adult education utilizes conceptual analysis approach in elucidating the concepts of adult education. Included in the concepts are the concept of adult education, objectives of adult education, and the process of education.